EFFECT OF VARIOUS SUSTAINED RELEASE POLYMERS ON FLOATING TABLETS OF CARVEDILOL PHOSPHATE-A COMPARATIVE STUDY - SHANKAR, K. RAVI; AMINABEE, SHAIK; LAKSHMI, KNV CHENCHU; REDDY, G. RAMANA; SHAIK, REEHANA; TIYAGURA, VINEETHA; SULTANA, SHAIK ALMAAS; BASHA, SHAIK; MOKESH SAI, KANDEPU; BHAGAVAN, JALADI; et al. (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to develop floating tablets of Carvedilol phosphate containing various excipients such as HPMC K100M, Carbopol, Polyox WSR, HPMC K4M, and sodium bicarbonate to generate gas. Additionally, the impact of DCP, spray dried lactose, and HPβCD on drug release was investigated. Methods: A total of eighteen formulations were prepared using the direct compression method and evaluated for hardness, drug content, friability, floating lag time, floatation time and drug release properties. Results: FTIR analysis confirmed that there were no chemical interactions between Carvedilol phosphate and the excipients used in the formulation of the floating tablets. Most of the Carvedilol phosphate floating tablets, except for F9 and F10, did not disintegrate in water, alkaline fluids (pH 7.4), or acidic aqueous solutions (pH 1.2). These tablets exhibited satisfactory quality attributes in terms of hardness, drug content, and friability, making them suitable for sustained release. The floating lag time of the tablets ranged from 25 seconds to 34 min, while the floating duration varied from 2 to 24 h. The drug release from the tablets was gradual and sustained over 12 h, depending on the composition of the tablets. Polyox WSR (F9 and F10) resulted in a rapid drug release, whereas an increase in the polymer concentration led to a decrease in the rate of drug release across all formulations. Conclusion: The study reveals that the use of hydrophilic polymers enhanced the drug release, whereas hydrophobic polymers decreased the drug release. As such, formulations, F11, F15, and F16, which gave 100% drug release within 12 h are finalized as the optimized formulations of Carvedilol phosphate floating tablet.